Pregnant Butch nine long months spent in drag - Summers, A.K (Soft Skull Press, 2014)
First pregnancy can be a fraught, uncomfortable experience for any woman, but for resolutely butch lesbian Teek Thomasson, it is exceptionally challenging: Teek identifies as a masculine woman in a world bent on associating pregnancy with a cult of uber-femininity. Teek wonders, Can butches even get pregnant?"Of course, as she and her pragmatic femme girlfriend Vee discover, they can. But what happens when they do? Written and illustrated by A.K. Summers, and based on her own pregnancy, Pregnant Butch strives to depict this increasingly common, but still underrepresented experience of queer pregnancy with humor and complexity--from the question of whether suspenders count as legitimate maternity wear to the strains created by different views of pregnancy within a couple and finally to a culturally critical and compassionate interrogation of gender in pregnancy.Offering smart, ambitious art, this graphic memoir is a must-read for would-be pregnant butches and anyone interested in the intersection of birth and gender, as well as a perfect queer baby shower gift and conversation starter for those who always assumed they "got" being pregnant.